IMPACT OF EMPLOYEE TRANSFERS AND PROMOTIONS ON PERFORMANCE AT THE BANK INDONESIA REPRESENTATIVE OFFICE IN PAPUA PROVINCE - Solihin, Solihin; Oktaviannur, M; Narundana, Vonny Tiara (Program Studi Magister Manajemen, 2024)
Abstract Employee performance at the representative office of Bank Indonesia Papua Province, which is based on quarterly performance reports. The cause of the decline in performance at the representative office of Bank Indonesia Papua Province is caused by several things, one of which is the Mutation and Promotion that applies at the representative office of Bank Indonesia Papua Province. The research was conducted to find out in an analysis related to the Effect of Mutation and Promotion of Employee Positions on the Performance of the Representative Office of Bank Indonesia Papua Province. The results of the research that have been carried out show that the validity and reliability of the questionnaire are declared valid and reliable, then through hypothesis testing all hypotheses are accepted and significant. The conclusion of this study is that mutase and promotion both partially and simultaneously affect the performance of the representative office of Bank Indonesia Papua Province